1990
DOI: 10.1101/gad.4.11.1910
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of Xenopus homeo box genes by mesoderm-inducing growth factors and retinoic acid.

Abstract: What is the nature of positional information during embryogenesis? By using Xenopus homeo box genes as anteroposterior (A-P) markers, we confirm the findings of others that mesoderm-inducing growth factors and retinoic acid (RA) can provide positional information along the axis of the body. Xenopus tissue culturemesoderm-inducing factor (XTC-MIF) selectively activates an anteriorly expressed homeo box gene {XlHbox 1), while basic fibroblast growth factor (bFGF) activates selectively a posteriorly expressed hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(91 citation statements)
references
References 36 publications
3
88
0
Order By: Relevance
“…This evidence suggests that HOX4C plays a distinct role in the initiation of limb formation. Several lines of evidence suggest that FGF has multiple effects on the expression of HOX genes (23,39,40). For example, in the developing mouse limb, Evx-1, a horneobox-containing gene, was recently identified as a downstream gene in the FGF signal transduction pathway in limb patterning (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence suggests that HOX4C plays a distinct role in the initiation of limb formation. Several lines of evidence suggest that FGF has multiple effects on the expression of HOX genes (23,39,40). For example, in the developing mouse limb, Evx-1, a horneobox-containing gene, was recently identified as a downstream gene in the FGF signal transduction pathway in limb patterning (41).…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of the limb bud has also been linked to the HOX D cluster (21,22). It has been shown that some HOX genes, such as XIHbox 6 and HOXD1, are activated by bFGF in Xenopus (23)(24)(25). Based on the above findings, we postulated that bFGF, through activation of a HOX gene, is involved in the proliferation and transformation of synovial fibroblasts in the rheumatoid joint.…”
mentioning
confidence: 99%
“…At the egg stage, at least four genes encoding retinoidresponsive nuclear receptors are already present in Xenopus (Blumberg et al, 1992). As is the case for other members of the Xenopus Hox 2 complex (i.e., Hox 2.5, 2.3, and 2.7; Cho and De Robertis, 1990;Leroy and De Robertis, 1992), treatment of embryos with retinoic acid increases steady state levels of Hox 2.4. Figure 7 presents the results of RNAse protection assays of embryos treated with retinoic acid.…”
Section: Hox 24 Expression In Xenopus Embryos Is Enhanced By Treatmementioning
confidence: 96%
“…For the animalhegetal conjugates, stage 8 blastula embryos were dechorionated manually and animal and vegetal fragments were dissected out in an agar dish containing 1 x MBS as described previously (Cho and De Robertis, 1990). For determination of the regionspecific expression of Hox 2.4, stage 14 and 26 embryos were dissected into fragments using a razor blade.…”
Section: Fertilization Microinjection and Dissection Of Embryosmentioning
confidence: 99%
See 1 more Smart Citation